Formação de agenda e formulação de uma política pública no Brasil: o caso do Fundo Social do Pré-Sal - Trojbicz, Beni (2014)
In order to understand the process that generates the Pre-Salt Social Fund, one needs to fully comprehend the new 2010 Brazilian oil regulation. This thesis analyses this regulation path, starting with the 1997 Oil Law (Lei do Petróleo), and evaluates how ideas and interests interact with institutional framework, politics and economic background, in order to create a new sectorial configuration. Combining Historical Neo-Institutionalism broad view with the Rational Choice Neo-Institutionalism robust methods for actors preferences modeling, this work points to actors preference historical determination. In empirical terms, it shows how economic conditions were critical for the Brazilian economic policy permeability to interests represented by multilateral institutions, as well, it explains oil reserves importance in the process, and finally points to a new reason for the Petrobras value increase after 1997.